THE RELATIONSHIP OF KNOWLEDGE ABOUT STROKE AND HEALTHY BEHAVIOR IN HYPERTENSION PATIENTS AT KARANGJAMBU HEALTH CENTER - Septavianada Jihan Azhar; Adiratna Sekar Siwi; Septian Mixrova Sebayang (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Hypertension or high blood pressure is a condition where the systolic blood pressure has increased above 140 mmHg and the diastolic blood pressure is above 90 mmHg with measurement twice in a calm body condition within a span of five minutes. One of the complications of hypertension that poses a threat is stroke. Attempts that can be done to reduce the rates of death and disability due to stroke, namely preventions by increasing knowledge of stroke and implementing healthy behavior for people with hypertension. This study was aimed to determine the relationship of knowledge about stroke with healthy behavior in patients with hypertension at Karangjambu Health Center. This study used quantitative methods with descriptive correlation design and used a cross sectional approach. The sampling technique used nonprobability accidental sampling with 66 respondents. Data were collected using the SRQ questionnaire for knowledge of stroke and HPLP II for the healthy behavior. Univariate analysis used descriptive correlation and bivariate analysis used the spearman rank test. Statistical test results obtained p value 0.001. It is concluded that there is a relationship between knowledge of stroke and healthy behavior in patients with hypertension at Karangjambu Health Center. The better the respondent's knowledge, the better the healthy behavior that is applied, thus the results of this study are important for Health Center officers in attempts to prevent stroke complications in patients with hypertension.